Every molecule tells a story - Cotton, Simon (Boca Raton, FL : CRC Press, 2012)
'Preface Everything that exists is made of atoms, and most of those substances contain groups of two or more of these bonded together to form molecules. Chemistry is the science of molecules. From cooking to medicine, from engineering to art, it is everywhere'--
'Written by a seasoned teacher, speaker, and writer in the field of chemistry, this text provides a guidance on chemicals that make life possible and enrich the senses, as well as those that endanger it. It combines the science and history of certain molecules and deals with the chemistry of each substance in an interesting and easily understandable manner. Topics covered include substances found in air and water, food, hydrocarbons, acids and alkalis, natural killers, unnatural killers, destructive molecules, pleasure molecules, natural healers, man-made healers, giant molecules, and vitamins'-- Provided by publisher.
Includes bibliographical references (p. 211-243) and index.
Keywords: Chemical bonds; Molecules